The influence of compensation, competency and organizational culture on commitment, and the implications for the performance of vocational school teachers - Dian Rostikawati; Azhar Affandi; Umi Rusilowati; Sidik Priadana; Iman Sudirman (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to explore the influence of compensation, competence, and school culture on teachers' work commitment and performance at vocational high schools (SMKs) in Tangerang Raya. Using a quantitative research design, data were collected from 330 permanent teachers through structured questionnaires. The analysis, conducted using Structural Equation Modeling (SEM), revealed that compensation, competence, and school culture significantly impact teachers' work commitment and performance. Among these variables, competence has the greatest influence, followed by compensation and school culture. The findings indicate that improving teacher competence through training and continuing education is crucial for enhancing their commitment and performance. Additionally, supportive school culture and adequate compensation are essential factors that can drive better teacher performance. This research provides valuable insights for education policymakers to formulate more effective strategies for enhancing vocational education quality in Indonesia, particularly in the Tangerang Raya region. The study underscores the importance of integrated efforts in improving compensation, competence, and school culture to enhance teacher commitment and performance, ultimately contributing to better education quality and more competent graduates.